1991
DOI: 10.1182/blood.v78.11.2834.2834
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of human myeloid leukemia cell line associated with the tyrosine-phosphorylation and activation of the proto-oncogene c-kit product

Abstract: We investigated the expression, degree of phosphorylation, and activation of the proto-oncogene c-kit product before and after stimulation with the c-kit ligand in a human factor-dependent myeloid leukemia cell line, MO7E. The culture supernatant of the BALB/3T3 fibroblast cell line, which contains the ligand for the murine c-kit product, was found to stimulate proliferation of the MO7E cell line in a dose-dependent manner. The proliferation was significantly inhibited by a tyrosine kinase inhibitor, genistein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…All three factors induced a rapid, transient, and concentration-dependent phosphorylation of several phosphoproteins, and for each factor the range of effective concentrations was similar for tyrosine phosphorylation and for proliferation of M07 cells, suggesting that the induction of tyrosine phoshorylation may be involved in triggering cell proliferation by growth factors. Some of the proteins phosphorylated on tyrosine in response to SF were unique; parts of the phosphorylated bands at = 145 kDa have recently been identified as autophosphosphorylation of c-hit in M07 cells (Kuriu et al, 1991). This finding further supports the concept of receptor autophosphorylation as a part of the signal transduction process of c-kit (Lev et al, 1991;Rottapel et al, 1991;Ullrich and Schlessinger, 1990).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…All three factors induced a rapid, transient, and concentration-dependent phosphorylation of several phosphoproteins, and for each factor the range of effective concentrations was similar for tyrosine phosphorylation and for proliferation of M07 cells, suggesting that the induction of tyrosine phoshorylation may be involved in triggering cell proliferation by growth factors. Some of the proteins phosphorylated on tyrosine in response to SF were unique; parts of the phosphorylated bands at = 145 kDa have recently been identified as autophosphosphorylation of c-hit in M07 cells (Kuriu et al, 1991). This finding further supports the concept of receptor autophosphorylation as a part of the signal transduction process of c-kit (Lev et al, 1991;Rottapel et al, 1991;Ullrich and Schlessinger, 1990).…”
Section: Discussionsupporting
confidence: 52%
“…Using monospecific antibodies to c-hit, we have recently shown that one of the tyrosine phosphorylated Table 1. bands in M 0 7 cells at -145 (140-150) is the c-kit receptor itself (Kuriu et al, 1991). No clear synergy was discovered a t the level of tyrosine phosphorylation of any of the proteins, and no additional phosphoproteins became apparent after combined stimulation with GM-CSF and SF or IL-3 and SF.…”
Section: S F Induces Rapid Tyrosine Phosphorylation In M 0 7 Cells Ofmentioning
confidence: 97%
“…Leukemic cells are known to express receptors for cytokines and to respond to these cytokines in terms of proliferation. Of note, several studies provided data demonstrating that c-kit and its ligand could be involved in the clonogenic growth of leukemic cells [55][56][57].…”
Section: Wild-type C-kit and Leukemiasmentioning
confidence: 99%
“…Genistein exhibits specific inhibitory activity against several receptor and nonreceptor tyrosine kinases (Hill et al, 1990;Kuriu et al, 1991;Trevillyan et al, 1990;Honna et al, 1990), and inhibits tyrosine phosphorylation events both at membrane level and distal to membrane-bound growth factor receptors (Rizzo et al, 1995). Since genistein inhibits topoisomerases I and II (Okura et al, 1988) and induces apoptosis of established leukaemic cell lines (Constantinou et al, 1990;Traganos et al, 1992), the possibility that this drug may exert effects other than tyrosine kinase inhibition can not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein, an isoflavone (5,7,4 naturally occurring, specific inhibitor of PTK catalytic activity present in soybeans (Akiyama et al, 1987). Genistein exerts specific inhibitory activity against receptor and cytoplasmic tyrosine kinases, including epidermal growth factor receptor, pp60 v-src , pp110 gag-fes , platelet-derived growth factor receptor, c-kit and p210 bcr/abl (Hill et al, 1990;Kuriu et al, 1991;Trevillyan et al, 1990;Honna et al, 1990). Genistein is competitive with respect to ATP and noncompetitive with the substrate and discriminates the differences in the catalytic site for ATP of the different protein kinases (Akiyama et al, 1987).…”
mentioning
confidence: 99%